A Comprehensive Analysis of Metabolite Profile and Phytochemical Composition of Ulva lactuca Macroalgae From The Coast of Banda Aceh, Indonesia - Akbar, Said Ali; Hasan, Muhammad; Afriani, Sari; Nuzlia, Cut; Zulfahmi, Ilham (Elkawnie, 2025)
Abstract: Marine macroalgae are known for their rich bioactive compounds, offering various pharmacological benefits. This research was conducted to analyze the phytochemical composition and metabolite profiles of Ulva lactuca, a marine macroalgae, along the coastal region of Banda Aceh, Indonesia. The research methodology encompassed three primary phases: assessment of antioxidant scavenging activity, determination of phytochemical composition, and in vivo metabolite profiling. The extract exhibited notable antioxidant activity, evidenced by its 47.22% inhibition rate. Spectral analysis via FTIR revealed prominent peaks at 1019 cm−1, 1654 cm−1, and 3352 cm−1, indicative of the presence of ethers, carbonyls, and hydroxyl groups, respectively. GC-MS analysis, coupled with a literature review, identified a total of 30 phytochemical compounds within Ulva lactuca, several of which possess significant bioactive properties with potential applications as antibacterial agents in both human and animal contexts. Consequently, Ulva lactuca demonstrates promising prospects as a source of antibacterial agents. The implications of this study suggest that Ulva lactuca could be developed as a natural alternative for antibacterial treatments, potentially reducing dependence on synthetic antibiotics in both healthcare and aquaculture industries. Abstrak: Makroalga dikenal karena kandungan senyawa bioaktifnya yang kaya, yang menawarkan berbagai manfaat farmakologis. Penelitian ini dilakukan untuk menganalisis komposisi fitokimia dan profil metabolit dari Ulva lactuca di sepanjang wilayah pesisir Banda Aceh, Indonesia. Metodologi penelitian mencakup tiga fase utama: penilaian aktivitas antioksidan, penentuan komposisi fitokimia, dan profil metabolit in vivo. Ekstrak menunjukkan aktivitas antioksidan yang signifikan, dibuktikan dengan tingkat inhibisi sebesar 47,22%. Analisis spektral menggunakan FTIR mengungkapkan puncak pada 1019 cm−1, 1654 cm−1, dan 3352 cm−1, yang menunjukkan adanya gugus eter, karbonil, dan hidroksi. Analisis GC-MS, yang dipadukan dengan tinjauan literatur, mengidentifikasi total 30 senyawa fitokimia dalam Ulva lactuca, beberapa di antaranya memiliki sifat bioaktif signifikan dengan potensi aplikasi sebagai agen antibakteri dalam konteks manusia dan hewan. Dengan demikian, Ulva lactuca menunjukkan prospek yang menjanjikan sebagai sumber agen antibakteri. Implikasi dari penelitian ini menunjukkan bahwa Ulva lactuca dapat dikembangkan sebagai alternatif alami untuk pengobatan antibakteri, yang berpotensi mengurangi ketergantungan pada antibiotik sintetis dalam industri kesehatan dan akuakultur.